AB1220 DISTRIBUTION OF RHEUMATOLOGISTS AND YOUNG RHEUMATOLOGISTS' ORGANIZATIONS ACROSS THE WORLD: STILL ROOM FOR IMPROVEMENT. (June 2019) - Najm, Aurelie; Spierings, Julia; Sciascia, Savino; Nikiphorou, Elena; Sepriano, Alexandre; Alunno, Alessia; ,
Abstract : Background: Rheumatology is a rapidly advancing specialty. The increasing understanding of autoimmune mechanisms and advanced therapies have improved care for patients with chronic inflammatory conditions immensely. National and international collaborations are growing and are key to scientific developments. Still, the number and geographical distribution of rheumatology organizations globally, is not known. Objectives: To gain further insights into the distribution of established and young rheumatologists' organizations beyond Europe. Furthermore, we intended to explore correlations between presence of rheumatology organizations and demographic and socio-economic parameters. Methods: A systematic online search was performed independently by three investigators (AN, SS, JS). Keywords used in the search related to three main themes (i) Rheumatology (rheumatology or rheumatologist(s) or rheumatism), (ii) Organizations (associations or young organization or society or group or association or league or federation) and (iii) country's name. All identified rheumatology organizations worldwide were reported. Countries were grouped in eight regions according to their geographic location. General demographic information (including population, area, pop. density, net migration, infant mortality, GDP, literacy, phones, arable, crops, climate, birth-rate, death rate) was retrieved from World Bank Open Data by one extractor (SS). Descriptive statistics and quartile distribution for each analysed variable were performed using Excel R (Microsoft Office) and SPSSR software R, using the total number of countries per region as the denominator. Results: Four international societies and three junior international organizations (EMEUNET, PANLAR joven, ALPAR Young rheumatologists) were identified. Out of the 227 countries assessed, 89 national rheumatology societies (39%) and seven junior national organizations were identified (n=4, 2%). Rheumatology societies were more frequent in Eastern Europe (n=18/27, 67%), Middle east (n=10/15, 67%) and Western Europe (n=19/29, 66%) (Figure 1 ). Rheumatology societies were more frequently found in countries in the upper quartiles (Q1) of population density, gross domestic product and literacy when compared to Q2-4 (as assessed for each variable, p<0.05). conversely, it was significantly less frequent in countries with high migration and infant mortality (q1 vs q2-3, p=0.043 and p=0.039, respectively). Conclusion: National rheumatology societies were identified in less than half the countries across the globe and were unequally distributed. We only found 7 national young organizations. Such organizations are needed, as trainees can highly benefit from educational and networking offers. Further steps will include the exploration of the impact and the reasons for lack of such establishments in some countries. Disclosure of Interests: Aurelie Najm: None declared, Julia Spierings Grant/research support from: Boehringer Ingelheim, Savino Sciascia: None declared, Elena Nikiphorou: None declared, Alexandre Sepriano: None declared, Alessia Alunno: None declared